Acute Mesenteric Ischaemia. (July 2014) - Schofield, Nick; Webb, Stephen T; Varcada, Massimo; Macfie, Alistair
Acute mesenteric ischaemia (AMI) is a surgical emergency, and has a high mortality. The term AMI covers arterial embolism, arterial thrombosis, non-occlusive mesenteric ischaemia and venous thrombosis which all lead to ischaemia/reperfusion syndrome of the bowel. Multi-detector row helical CT (MDCT) technology has dramatically improved the performance of CT by allowing rapid volumetric data acquisition to provide increased resolution, leading to better identification of the site, level and cause of ischaemia. CT angiography for diagnosing mesenteric ischaemia is now highly sensitive and specific, and should be used as first line when AMI is suspected. The aim of management is to restore intestinal blood flow in a timely manner. Therapeutic decisions are based on the presence of peritonitis, the presence of irreversible ischaemia or infarcted segments of the bowel, the general condition of the patient and the pathophysiological process underlying the ischaemia. AMI remains a challenging condition with high mortality. There is a need for good general surgical cover on the intensive care unit, with continuing care and clinical review by experienced senior surgeons with an interest in this condition.